The deployment of performance measurement system under the supply chain management environment: the case of Malaysian manufacturing companies - Ahmad, Kamilah; Mohamed Zabri, Shafie (The Academy of Business and Retail Management, 2018)
Performance measurement system in supply chain management (SCM) has been receiving increasing attention by business organizations as a way to evaluate efficiency in supply chain activities. Assessing the performance of supply chain uncovers the gap between planning and actual performance as to trace the potential problems thus ascertain necessary areas for improvement. This research aims to investigate the application of performance measurement system in SCM as well as exploring its relationship with organization’s performance among Malaysian manufacturing firms. By utilizing the questionnaire method, respondents involved were requested to indicate the extent to which they use a number of 24 selected performance measures that are related to SCM. The results show that the majority of the observed manufacturing firms utilize specific performance measurement tools in evaluating the supply chain performance. The current performance measurement techniques, the Balanced Score Card is adopted by around a quarter of the total responding firms followed by Supply Chain Operations References Model – SCOR, which attracts total users of only a fifth of the total respondents. In particular, performance measures under customer service category recorded the highest number of usage followed by cost-based performance measures and operations management. The results of this investigation also unveil few major points that are important to be highlighted. Firstly, the obtained outcomes of this study bring to light the significant relationships between the utilization of supply chain performance measures under customer service, operations management and organizational performance. In addition, this study discovered a significant correlation between the size of the organization and the extent of use of supply chain performance measures and how these two variables positively correlated. Lastly, the findings also suggested that the performance measures for SCM has been playing a crucial role in enhancing the performance of the organizations and is increasingly operated as the firms grow in size. Based on the brief highlighted points listed above, it is not an exaggeration to say that this research contributes new information to the body of knowledge in performance measurement system in SCM and its associations with organizational performance.